Basic principles of information technologies use in the improvement in training of the first-year students of medical universities - O. I. Kefeli-Yanovska (Zaporožskij Medicinskij Žurnal)
The principles of the use of information technology for teaching students at the medical university were discussed. Emphasizes the idea that, despite the rapid development of information and communication technologies in education problem of systematization, individualization of the educational process, adaptive learning are not considered. In this regard, the seven most important principles are justified with the basic subjects training (anatomy, histology etc.).